Comparison of memory B-Cell immune responses among different age groups after oral cholera vaccination - Azad, Abul Kalam (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2011